1991
DOI: 10.1063/1.349419
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis, microstructure, and magneto-optical recording in Co/Pt and Co/Pd multilayers

Abstract: The factors that influence the coercive field Hc and the shape of the magnetic hysteresis loop for Co/Pt multilayers (MLs), applied as a magneto-optical (MO) recording medium, have been investigated. The hysteresis loop of MLs, made by evaporation of Kr sputtering, became more rectangular when the total film thickness was reduced, i.e., the saturation field Hs decreased and the nucleation field Hn increased. Hs was calculated using a stripe domain model and Hn was modeled assuming that nucleation took place at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 25 publications
4
41
0
Order By: Relevance
“…As expected the XRD measurements reveal a clear enhancement of the ͑111͒ film texture with increasing Pt seed layer thickness. Although the more perfect initial Co/ Pt growth on thicker Pt seed layers results in a well-known increase of the coercive field, 20 the perpendicular exchange-bias field remains constant at about 8 mT ͓see Fig. 2͑c͔͒.…”
mentioning
confidence: 99%
“…As expected the XRD measurements reveal a clear enhancement of the ͑111͒ film texture with increasing Pt seed layer thickness. Although the more perfect initial Co/ Pt growth on thicker Pt seed layers results in a well-known increase of the coercive field, 20 the perpendicular exchange-bias field remains constant at about 8 mT ͓see Fig. 2͑c͔͒.…”
mentioning
confidence: 99%
“…This means that the electron tunneling does not occur directly into the Co, but rather into the Pt surface atoms that are spin polarized, due to the exchange interaction with the underlying Co. 36 ͑ii͒ We do not expect the polarization of the electronic states to be uniform over the sample surface, because the Pt/Co multilayer is constituted of microcrystallites with a diameter of 10 to 20 nm, 34 as we also verified with STM measurements.…”
Section: Discussionmentioning
confidence: 51%
“…It is well known that tunneling is not inhibited by a contamination layer, and that Pt/Co multilayers are resistant to oxidation. 34 Nevertheless, the operation under ambient conditions adds uncertainty to the value of the surface polarization. From the previous statements, we believe that the average polarization of our sample surface should be more than an order of magnitude lower than of pure Co; however, at selected sites, we assume that a reasonable upper limit for the polarization ͉P (G t )͉ is about 0.1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming an exchange stiffness constant (A) of 1.8 pJ m −1 (Zeper et al, 1991) the domain wall width π A/K eff is found to be 8.6 nm and the exchange length 2A/µ 0 M 2 s is found to be 4 nm. Since the cross dimensions are large compared to the film thickness, domain wall width and exchange length, the Hall cross area can in essence be considered as a thin film.…”
Section: Structure and Magnetic Properties Of The Continuous Filmmentioning
confidence: 99%